Small business trainers in Jamaica: Their accomplishments and aspirations: report of the first Annual Meeting held 3-4 December 1876, Pine Grove, Jamaica - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
82 páginas